ANALISIS KEMAMPUAN BERPIKIR KRITIS SISWA DALAM MENYELESAIKAN SOAL HOTS DITINJAU DARI KECERDASAN LOGIS MATEMATIS - Rika Juwita (INSPIRAMATIKA, 2021)
This research aims to describes the critical thinking ability of students in solving HOTS problems with high, medium, and low mathematical logic intelligence. This research is a descriptive research with a qualitative approach. The subjects of this research were 6 students of VIII-A grade at SMP Negeri 1 Deket in the 2019/2020 academic year. The determination of the subject was based on the result of the mathematical logic intelligence test. The instrument that was given to the research subjects consisted of a description test consisting of 2 questions. The data used are test results and the results of interview interviews. Based on the analysis of the data that has been done, the results of this research indicate that: (1) the critical thinking ability of students in solving HOTS problem with high mathematical logic intelligence indicate that students can fulfill four indicators of critical thinking ability, namely interpretation, analysis, evaluation, inference, and included in TKBK 4 (very critical); (2) the critical thinking ability of students in solving HOTS problem with medium mathematical logic intelligence indicate that students can fulfill three indicators of critical thinking ability, namely interpretation, analysis, evaluation, and included in TKBK 3 (critical); (3) the critical thinking ability of students in solving HOTS problem with low mathematical logic intelligence indicate that students can fulfill one indicator of critical thinking ability, namely interpretation and included in TKBK 1 (less critical).